The performance appraisal on internet dial-up service: a cast study on TMnet 1515 by Telekom Multimedia - Ismail, Mohd Faizal (2001)
Service performance is one of the indicator to determine its positioning after a great effort and strategies spent on the service. This research would be able to determine the strength and weaknesses of the service- provided the customers. A descriptive study has been organized to assist the Internet Service Provider in evaluating their level of performance. The objective of this study is to measure the performance of 8 critical areas of Internet service from the experience of 58 respondents. A set of questionnaire on the critical areas was distributed to the- respondents’ e-mail account. It was revealed that account connection was low performing mostly in registration process. As in dialing process, there were low performance in number of attempts and the time taken to connect. As for transmission, the speed was mostly well performing except for the interruption on the connection. There was nor difficulty- in setting up- e-mail account. However the speed of transmitting and receiving e-mails were slow. The content of the service provider’s homepage was useful but unattractive. Most of them claimed that the access rate is uncompetitive. All respondents feel convenient with the payment channel provided. Content of the bills were accurate- and easy to understand but there are- respondents who- did not receive their-bills. Only one third of the respondents lodged complaints or enquiry by visiting the outlet and via e-mail. The employees of the outlet were helpful and friendly. However, there was no reply for those who sent e-mails to the customer service. Finally, recommendations and conclusion have been made based on the objectives and results of the-findings. It would be more towards improving the Internet dial-up service towards higher quality and total customer satisfaction.